Health, well-being and education: Building a sustainable future. The Moscow statement on Health Promoting Schools. Issue 1 (18th March 2020) - Dadaczynski, Kevin; Jensen, Bjarne Bruun; Viig, Nina Grieg; Sormunen, Marjorita; von Seelen, Jesper; Kuchma, Vladislav; Vilaça, Teresa
Abstract : Purpose: The purpose of this paper is to introduce the official statement of the Fifth European Conference on Health-Promoting Schools. Design/methodology/approach: The Fifth European Conference on Health-Promoting Schools was held on 20–22 November 2019 in Moscow, Russian Federation, with over 450 participants from 40 countries. A writing group was established to prepare a draft version of the statement before the conference. On the basis of an online and offline feedback process, the opinions of the participants were collected during the conference and included in the finalisation of the statement. Findings: The final conference statement comprises six thematic categories (values and principles; environment, climate and health; schools as part of the wider community; non-communicable diseases (NCDs); evidence base; and digital media), with a total of 23 recommendations and calls for action. Originality/value: The recommendations and calls for action reflect current challenges for Health Promoting Schools in Europe. They are addressed to all actors in governmental, non-governmental and other organisations at international, national and regional levels involved in health promotion in schools and are to be applied for the further development of the concept.